SIFAT FISIKA DAN MEKANIKA KAYU JELUTUNG (DYERA COSTULATA) DARI HUTAN TANAMAN RAKYAT KALIMANTAN TENGAH - Rio Ilhamsyah; Wiwin Tyas Istikowati; Rosidah Radam (Jurnal Sylva Scienteae, 2023)
The physical and mechanical of jelutung wood come from the community plantation forest, village of Kelampangan, Sebangau district, Palangka Raya city, Central Kalimantan, It was observed in this study with the aim of deciding to match the use of jelutung wood according to the properties of physics and mechanics. The wood cut was taken at 50  5  5 centimeters for MOE's test and at 50  3  3 centimeters for testing the mor taken from three jelutung wood. Test samples using universal testing devices mechine (utm) Manuals and digital calipers to test shrink on jelutung wood. The coinage of jelutous wood range from 0.38, 0.37 and 0.34 and based on an average of 0.36 wood that is included in the strong IV class. the rate of depreciation in tangential and radial directions ina sequence is 0.28 and 0.11. MOE's two-time repeat sequence has 27.6 and 23.6. MOR tests with double repetition also have a value of 46.35 and 216.2.Pengujian sifat fisika dan mekanika kayu jelutung berasal dari kawasan Hutan Tanaman Rakyat desa Kelampangan, Kecamatan Sebangau, Kota Palangka Raya, Kalimantan Tengah diamati pada penelitian ini dengan tujuan untuk menentukan kesesuaian penggunaan kayu jelutung berdasarkan sifat fisika dan mekanika. Potongan kayu diambil sebesar sebesar 50 5  5 cm untuk pengujian MOE dan sebesar 50  3  3 cm untuk pengujian MOR yang diambil dari 3 bagian kayu jelutung. Sampel diuji menggunakan alat Universal Testing Mechine (UTM) manual dan kaliper digital untuk menguji penyusutan pada kayu jelutung. Berat jenis kayu jelutung berkisar dari 0,38, 0,37 dan 0,34 serta berdasarkan rata-rata yang bernilai 0,36 kayu ini termasuk dalam kelas kuat IV. Nilai penyusutan pada arah tangensial dan radial secara berurutan adalah 0,28 dan 0,11. Pengujian MOE sebanyak 2 kali pengulangan secara berurutan memiliki nilai 27,6 dan 23,6. Pengujian MOR dengan 2 kali pengulangan secara berurutan juga memiliki nilai 46,35 dan 216,2.